Psychosocial Interventions and Wellbeing in Individuals with Diabetes Mellitus: A Systematic Review and Meta-Analysis - Pascoe, Michaela C.; Thompson, David R.; Castle, David J.; Jenkins, Zoe M.; Ski, Chantal F. (Frontiers in Psychology, 2017)
Abstract Purpose: A number of studies, including systematic reviews, show beneficial effects of psychosocial interventions for people with diabetes mellitus; however, they have not been assessed using meta-analysis. The purpose of this meta-analysis of randomised controlled trials is to investigate the effects of psychosocial interventions on depressive and anxiety symptoms, quality of life and self-efficacy in individuals with diabetes mellitus. Methods: The databases Pubmed, MEDLINE, CINAHL, PsycINFO, Scopus, Web of Science and SocINDEX were searched with no year restriction. Eligible studies were randomised controlled trials published in English that included individuals diagnosed with diabetes mellitus, aged 18 years or above, who engaged in a psychosocial intervention, with outcome measures addressing depressive or anxiety symptomology, quality of life or self-efficacy. Eligible studies needed to compare the intervention to usual care. Study selection was completed using Covidence and meta-analysis was undertaken using Comprehensive Meta-Analysis software. Results: Seven studies were included in the meta-analysis. Five studies investigated the effects of psychosocial interventions and showed a medium to large benefit for depressive symptoms (SMD: -0.70; CI:-1.27, -0.13) which persisted at follow up (SMD:-1.54, CI:−2.97, −0.12). Similar results were not seen immediately post-intervention in the three studies that assessed anxiety symptoms (SMD: -0.30; CI:-0.69, 0.10); however, a medium beneficial effect was seen at follow up (SMD=-0.61, CI=-0.92 to-0.31). Small benefits were seen in the three studies assessing quality of life outcomes (SMD: 0.30, CI: 0.06, 0.55). No benefit was seen inthe two studies assessing self-efficacy (SMD: 0.23, CI:-0.11, 0.57). Conclusions: The results of the current study provide preliminary evidence that psychosocial interventions, compared to usual care, reduce depressive symptoms, and may improve quality of life in individuals with diabetes. However, only a few studies were included and the clinical significance of these findings is unknown.